2006
DOI: 10.1007/s11262-006-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the repeat long regions of oncogenic and attenuated pathotypes of Marek’s disease virus 1

Abstract: The nucleotide sequences of the terminal repeat long (TR(L)) and internal repeat long regions (IR(L)) in the genomes of 13 strains of Marek's disease virus type 1 (MDV-1) were determined and represent the largest collection of sequencing data from a contiguous region (12.8 kb) in the serotype 1 genomes. The collection of strains used in this study has been well characterized with respect to their virulence and contains members of each pathotype (4 attenuated, 1 mildly virulent, 3 virulent, 2 very virulent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…This region of tandem repeats in GaHV-2 isolates is hypervariable (Spatz and Silva 2007a): there are between 0 and 13 copies of the 60-bp direct repeat, depending on the viral strain. The P1D39 construct obtained from RB-1B Bacmide DNA contains three copies, with 63 nt of upstream and 10 nt of downstream sequences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This region of tandem repeats in GaHV-2 isolates is hypervariable (Spatz and Silva 2007a): there are between 0 and 13 copies of the 60-bp direct repeat, depending on the viral strain. The P1D39 construct obtained from RB-1B Bacmide DNA contains three copies, with 63 nt of upstream and 10 nt of downstream sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Several strains of GaHV-2 with different oncogenic capacities, correlated with their level of pathogenicity, have been isolated and partially sequenced. Recent published alignments of the sequences from a panel of 14 strains, including the promoter and part of the LAT gene, have shown that all the virulent, very virulent, and hypervirulent oncogenic GaHV-2 strains harbor two or more 60-bp tandem repeats (Spatz and Silva 2007a). By contrast, avirulent, mildly virulent, and vaccine strains have no copies of the tandem repeat.…”
Section: Discussionmentioning
confidence: 99%
“…The 177 bp insertion in the meq gene has been associated with isolates of lower virulence (Shamblin et al, 2004;Spatz & Silva, 2007). However, all five Australian isolates showed an insertion of 177 bp but, based on the results of the pathotyping experiment, were classified as virulent or very virulent according to the classification system of Witter (1997), inducing MD tumours in 53 to 94% of challenged chickens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sequences were compared with the meq gene of cloned isolate of the vaccinal MDV1 isolate Rispens/CVI988 vaccine strain (Spatz & Silva, 2007; GenBank accession number DQ534538). This isolate had been passaged 27 times in chicken embryo fibroblast cell culture and was obtained from Intervet (Boxmeer, the Netherlands) (Spatz & Silva, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation